2018
DOI: 10.1039/c8ra06048g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photoluminescence properties of novel far-red-emitting BaLaMgNbO6:Mn4+ phosphors for plant growth LEDs

Abstract: Mn4+-activated BaLaMgNbO6 far-red emitting double-perovskite phosphors with internal quantum efficiency up to 52% were developed for potential application in plant growth LEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 73 publications
(81 reference statements)
0
35
0
Order By: Relevance
“…The PLE spectra of all compounds showed two excitation bands in 250‐300 nm and 350‐450 nm regions, with former being the most intense one. The excitation in the 350‐450 nm region are due to characteristic excitation band of Eu 3+ ion, while that in the 250‐300 nm region correspond to charge transfer band (CTB) between Eu 3+ and the surrounding oxygen anions . The excitation spectra showed that the PLE spectra of both BLCN:Eu and BLMN:Eu are blue shifted with respect to the compound BLN:Eu.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The PLE spectra of all compounds showed two excitation bands in 250‐300 nm and 350‐450 nm regions, with former being the most intense one. The excitation in the 350‐450 nm region are due to characteristic excitation band of Eu 3+ ion, while that in the 250‐300 nm region correspond to charge transfer band (CTB) between Eu 3+ and the surrounding oxygen anions . The excitation spectra showed that the PLE spectra of both BLCN:Eu and BLMN:Eu are blue shifted with respect to the compound BLN:Eu.…”
Section: Resultsmentioning
confidence: 98%
“…This indicates more degree of freedom is required at the oxygen site. Though in the recent work by Qi Sun et.al., where the Fm3¯m space group was assigned for manganese doped BLMN compound, the values of Biso parameters and other structural parameters were not reported . Depending upon the tilting of the octahedral double perovskites with rock‐salt type cation ordering, crystal structure can adopt various symmetries and space groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the indoor plant cultivation attracted great interest since it can supply suitable living conditions for plant such as sufficient water, rich nutrition and adjustable temperature . The different wavelength lights have different effects on the plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
“…As one of non‐rare‐earth activators for red‐emitting phosphors, Mn 4+ ion with 3 d 3 electron configuration is attracting considerable interest because it can show broad absorption band in the range from 220 to 570 nm and exhibit red or deep red emission in the region from 600 to 790 nm due to the 2 E→ 4 A 2 transition . Mn 4+ ion can usually be stable in octahedral environments and substitute for the Al 3+ , Sc 3+ , Ga 3+ , Ti 4+ , Si 4+ , Ge 4+ , Zr 4+ , Sn 4+ , Ta 5+ , Nb 5+ , Sb 5+ , Te 6+ , Mo 6+ , and W 6+ sites in octahedral cell and form the octahedral center in host lattice . The luminescence properties of Mn 4+ ‐doped phosphors can be affected by the co‐valency of the “Mn 4+ ‐ Ligand” bonding and the host crystal field environment.…”
Section: Introductionmentioning
confidence: 99%